(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The digital transformation in bank management is reshaping the industry by enabling banks to provide personalized, efficient, and customer-centric services. This transformation leverages technology-driven marketing strategies to enhance customer experience, redefine relationships, and strengthen customer loyalty. This article explores how digital transformation, including data analytics, artificial intelligence (AI), and customer relationship management (CRM) platforms, empowers banks to understand and meet customer needs. Through an in-depth analysis of contemporary marketing techniques, this research highlights the benefits, challenges, and future directions of digital transformation in banking.